On the Slow Diffusion of Point-of-Care Systems in Therapeutic Drug Monitoring - Sanavio, Barbara; Krol, Silke (Frontiers in Bioengineering and Biotechnology, 2015)
Recent advancements in point-of-care technologies show great transformative promises for personalized preventative and predictive medicine. However, fields like therapeutic drug monitoring, that first allowed for personalized treatment of patient’ disease, still lag behind in the widespread application of point-of-care devices for monitoring of patients. Surprisingly, very few applications in commonly monitored drugs, such as anti-epileptics, are paving the way for a point of care (PoC) approach to patient’ therapy monitoring, compared to other fields –like intensive care cardiac markers monitoring, glycemic controls in diabetes, or bench-top hematological parameters analysis at the local drug store. Such delay in the development of portable fast clinically effective drug monitoring devices is in our opinion due more to an inertial drag on the pervasiveness of these new devices into the clinical field than a lack of technical capability. At the same time, some very promising technologies failed in the clinical practice for inadequate understanding of the outcome parameters necessary for a relevant technological breakthrough that has superior clinical performance. We hope, by overviewing both therapeutic drug monitoring practice and its yet unmet needs and latest advancement in micro and nanotechnology applications to PoC clinical devices, to help bridging the two communities, the one exploiting analytical technologies and the one mastering the most advanced techniques, into translating existing and forthcoming technologies in effective devices.